2021
DOI: 10.26434/chemrxiv-2021-zpfxf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organophotocatalytic Late-stage N-CH3 Oxidation of Trialkylamines with O2 in Continuous Flow

Abstract: We report an organophotocatalytic, N-CH3-selective oxidation of trialkylamines in continuous flow. Based on the 9,10-dicyanoanthracene (DCA) core, a new catalyst (DCAS) was designed with solubilizing groups for processing in flow which allowed harnessing of O2 as a benign reagent for late-stage photocatalytic N-CH3 oxidation of natural products and active pharmaceutical ingredients. These substrates bear functional groups which are not tolerated by previous methods. The organophotocatalytic process benefited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Mechanistic investigations, carried out by light-excitation of the benzophenone 47 a showed that the indole derivative 46 quenches its emission, and the reactivity is greatly decreased in presence of DABCO or oxygen as tripletexcited-state quencher. [44] The absorbance and emission profiles of the benzophenone solution remained unchanged upon adding indole 46, thus excluding any ground-state or excited-state association. Moreover, ΔG PET calculations showed that a PET pathway was not feasible for benzophe-none (ΔG PET = + 28.83 kcal mol À 1 ).…”
Section: Benzils and Benzophenonesmentioning
confidence: 96%
“…Mechanistic investigations, carried out by light-excitation of the benzophenone 47 a showed that the indole derivative 46 quenches its emission, and the reactivity is greatly decreased in presence of DABCO or oxygen as tripletexcited-state quencher. [44] The absorbance and emission profiles of the benzophenone solution remained unchanged upon adding indole 46, thus excluding any ground-state or excited-state association. Moreover, ΔG PET calculations showed that a PET pathway was not feasible for benzophe-none (ΔG PET = + 28.83 kcal mol À 1 ).…”
Section: Benzils and Benzophenonesmentioning
confidence: 96%
“…Benzils were also tested using Mechanistic investigations, carried out by light-excitation of the benzophenone 47 a showed that the indole derivative 46 quenches its emission, and the reactivity is greatly decreased in presence of DABCO or oxygen as tripletexcited-state quencher. [44] The absorbance and emission profiles of the benzophenone solution remained unchanged upon adding indole 46, thus excluding any ground-state or excited-state association. Moreover, ΔG PET calculations showed that a PET pathway was not feasible for benzophe-none (ΔG PET = + 28.83 kcal mol À 1 ).…”
Section: Benzils and Benzophenonesmentioning
confidence: 96%